Exploring the causes of the decline in student visits to the STIKes Binalita Sudama Medan library - Raimah, Raimah; Yusniah, Yusniah (Jurnal Informatio, 2025)
Background: The rate of student visits to the STIKes Binalita Sudama Medan library has experienced a significant and drastic decline in recent years. This phenomenon presents a crucial issue as it directly impacts the low utilization of verified academic information sources by students. Furthermore, this situation threatens the fundamental role of the library as a center for learning and intellectual development within the higher education ecosystem, thus requiring an in-depth exploration to understand its root causes.Purpose: This study aims to comprehensively explore the underlying factors contributing to the decline in student visits to the library. Additionally, it seeks to identify and analyze the effectiveness of relevant and contextually appropriate strategies that can be implemented to revitalize the library's role.Methods: This research employed a descriptive qualitative approach, utilizing a case study method to gain a holistic understanding. Data were collected through technique triangulation, which included in-depth interviews, participant observation, and a documentation study. Research informants, consisting of librarians and students, were selected using a snowball sampling technique until data saturation was achieved.Results: The findings indicate that the causes for the decline in visits are multifaceted, stemming from both internal factors (student attitudes and digital preferences) and external factors (inadequate facilities, collections, and promotion). Existing strategies, such as lecturer collaboration and friendly service, have not been optimally effective.Conclusions: The decline in visits is influenced by internal factors and significantly exacerbated by external factors, namely the library's failure to meet basic user expectations. This study provides a critical diagnostic contribution for library management to reformulate more effective, user-centered strategies aimed at enhancing the library's appeal and relevance.